A finite element method-based potential theory approach for optimal ice routing - Piehl, Henry; Milaković, Aleksandar-Saša; Ehlers, Sören (Journal of Offshore Mechanics and Arctic Engineering, 2017)
Shipping in ice-covered regions has gained high attention within recent years. Analogous to weather routing, the occurrence of ice in a seaway affects the selection of the optimal route with respect to the travel time or fuel consumption. The shorter, direct path between two points—which may lead through an ice-covered area—may require a reduction of speed and an increase in fuel consumption. A longer, indirect route, could be more efficient by avoiding the ice-covered region. Certain regions may have to be avoided completely, if the ice thickness exceeds the ice-capability of the ship. The objective of this study is to develop a computational method that combines coastline maps, route cost information (e.g., ice thickness), transport task, and ship properties to find the optimal route between port of departure, A, and port of destination, B. The development approach for this tool is to formulate the transport task in the form of a potential problem, solve this equation with a finite element method (FEM), and apply line integration and optimization to determine the best route. The functionality of the method is first evaluated with simple test problems and then applied to realistic transport scenarios.